2013
DOI: 10.1038/nchem.1788
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assembly of complex cyclopentanes employing chiral, α,β-unsaturated acylammonium intermediates

Abstract: Toward improving synthetic efficiency, organic chemists have turned to bioinspired organocascade or domino processes that generate multiple bonds and stereocenters in a single operation. However, despite the great importance of substituted cyclopentanes, given their prevalence in complex natural products and pharmaceutical agents, the rapid, enantioselective assembly of these carbocycles lags behind cyclohexanes. Herein, we describe a novel Michael-aldol-β-lactonization organocascade process for the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 62 publications
3
57
0
2
Order By: Relevance
“…34 ) were obtained in high enantiomeric purity and good yields using Birman’s homobenzotetramisole (HBTM) catalyst with ketomalonates and commodity acid chlorides. 15 Importantly, this organocascade highlighted the triple reactivity of the unsaturated acylammonium salt intermediate in its ability to participate first as an electrophile, then a nucleophile through the ammonium enolate, and finally as an electrophile through the acylammonium intermediate. The proposed organocascade involves generation of ammonium enolate 37 by the Michael addition of malonate anion 36 to the α,β-unsaturated acylammonium chloride 35 .…”
Section: αβ-Unsaturated Acylammonium Saltsmentioning
confidence: 96%
See 1 more Smart Citation
“…34 ) were obtained in high enantiomeric purity and good yields using Birman’s homobenzotetramisole (HBTM) catalyst with ketomalonates and commodity acid chlorides. 15 Importantly, this organocascade highlighted the triple reactivity of the unsaturated acylammonium salt intermediate in its ability to participate first as an electrophile, then a nucleophile through the ammonium enolate, and finally as an electrophile through the acylammonium intermediate. The proposed organocascade involves generation of ammonium enolate 37 by the Michael addition of malonate anion 36 to the α,β-unsaturated acylammonium chloride 35 .…”
Section: αβ-Unsaturated Acylammonium Saltsmentioning
confidence: 96%
“…This results in a three component organocascade affording the complex cyclohexyl fused-tricyclic β-lactone 44 with four contiguous stereocentres with both high enantio- and diastereoselectivity (Scheme 8). 15 …”
Section: αβ-Unsaturated Acylammonium Saltsmentioning
confidence: 99%
“…Romo et al were able to synthesize the required bicyclic fragment, as shown in Scheme 5 [25]. This synthetic methodology is a variant of the previously reported procedure by Zhong et al [26].…”
Section: Non-chiral Acids or Bases For The Synthesis Of Bicyclo[3mentioning
confidence: 99%
“…7 These N-heterocyclic carbene (NHC) catalyzed reactions require either a stoichiometric amount of oxidant or functionalized aldehydes or esters as starting materials and have focused primarily on acyclic 1,3-dicarbonyl compounds. 8 These limitations, coupled to our recent studies of chiral α ,β -unsaturated acylammonium salts enabling Michael-aldol-β -lactonization, 9 Michael-proton transfer-lactamization, 10 and Diels-Alder-lactonization 11 organocascades, prompted us to reinvestigate the original idea of making cyclic enol lactones from unsaturated acid derivatives through organocatalysis with achiral and chiral Lewis bases under mild conditions. 12 In particular, the use of mono-and bicyclic 1,3-dicarbonyls in these reactions have not been described and thus we focused on these substrates.…”
Section: Graphical Abstractmentioning
confidence: 98%